2021
DOI: 10.1002/dc.24725
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of endobronchial ultrasound combined with rapid on‐site evaluation of transbronchial lung biopsy for peripheral pulmonary lesions

Abstract: Abstrac Background Rapid on‐site evaluation (ROSE) has the potential to increase endobronchial ultrasound (EBUS) guide transbronchial lung biopsy (TBLB) accuracy in the diagnosis of peripheral pulmonary lesions (PPLs). However, studies have reported controversial results. The aim of the study was to evaluate the diagnostic value of EBUS‐TBLB combination with ROSE in PPLs. Methods A total of 152 patients with PPLs underwent EBUS were enrolled and completed this study. Patients were divided into EBUS combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
1
14
2
1
Order By: Relevance
“…Our study has confirmed the performance of ROSE that it is likely to improve diagnostic yield especially for size of lesion < 2 cm. In disagreement with previous data suggesting reduced operation time in ROSE group [ 12 ], we reported that ROSE could shorten the diagnosis time, and improve cost-effectiveness for R-EBUS patients. On the basis of ROSE findings consistent with subsequent final pathologic diagnosis, it supports our approach of termination of procedure in the event of ROSE revealing malignancy and inflammation without further sampling.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our study has confirmed the performance of ROSE that it is likely to improve diagnostic yield especially for size of lesion < 2 cm. In disagreement with previous data suggesting reduced operation time in ROSE group [ 12 ], we reported that ROSE could shorten the diagnosis time, and improve cost-effectiveness for R-EBUS patients. On the basis of ROSE findings consistent with subsequent final pathologic diagnosis, it supports our approach of termination of procedure in the event of ROSE revealing malignancy and inflammation without further sampling.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, limited data are available concerning the application of ROSE during R-EBUS TBB in the diagnosis of PPLs [ 12 14 , 18 ]. A prospective RCT enrolling 152 patients with PPLs suggested that ROSE could improve the diagnostic yield and shorten the operation time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations